Design and Foundation Load Demand Comparative Study of Engineered Timber Building Versus Steel-Concrete Solution - Ling, Zi He; Yeoh, Eng Chuan (Recent Trends in Civil Engineering and Built Environment, 2022)
Industrial building nowadays are built using framing system due to the construction is fast and can serve many purpose for the building. A framing structural building can provide more space because it have less column taking up the space. The objective of this study is to perform design of an engineered timber building and the similar layout with a steel-concrete design solution and to determine the foundation load demand for both the engineered timber building and steel-concrete solution and also to produce an easy to use design spreadsheet for the engineered timber building. Two standard code of practice will be using on the design of the building which is Eurocode 3 for steel structure and Eurocode 5 for engineered timber Specific design guide NelsonPine LVL is also used for LVL engineered timber properties. In this study, we are going to perform design that carry load from the roof and 1st floor. Slab on steel building will be using precast concrete and slab on engineered timber will be using Timber-concrete composite (TCC). Loading analysis is carried out to determine the maximum shear force and maximum bending moment. Total axial load on the column is determine to obtain foundation load demand between steel building and engineered timber building. A simple design spreadsheet for simply supported LVL beam and LVL column will be produced for designing engineered timber building to speed up the designing process.